The construction of death rituals: A phenomenological study of the Balinese Buddhist community in Central Lampung - I ketut Damana (Cendikia : Media Jurnal Ilmiah Pendidikan, 2026)
Death ritual in the Balinese Buddhist community in Central Lampung is practice religious that brings together Buddhist teachings, traditions Balinese ancestors, and dynamics life diaspora communities. Previous studies about Buddhist death rituals in general focus on teachings about death, stages ceremony, or function social rituals in Buddhist society as a whole general. However, experience subjective and construction the meaning of death rituals in the Balinese Buddhist community in the area transmigration Still limited. The gap This important reviewed Because the Balinese Buddhist community in Central Lampung is undergoing a process of adaptation. different religions and cultures? from Balinese people in the area origin. Research This aim analyze construction the meaning of death rituals in the Balinese Buddhist community in Central Lampung through approach phenomenology. Research use method qualitative with approach phenomenology. Informant totaling 8 informants, consisting of on one priest, one figure customs Bali, one chairman Buddhists, two member family, two Buddhists, as well as One member Balinese Buddhist community. Informant chosen purposively based on performance of death rituals. Data is collected through observation, interview in-depth, and documentation, then analyzed through data reduction, data presentation, data extraction conclusions and interpretations experience subjective informant. Research results identify four theme main. First, the ritual is interpreted as respect final to ancestors. Second, the ritual becomes means strengthening hope on journey awareness going to birth back more? Good. Third, rituals function strengthen solidarity and involvement citizens. New study This lies in the explanation of death rituals as room negotiation Balinese-Buddhist identity in community people, which was formed through interaction Buddhist teachings, traditions ancestors, spiritual experiences, and relationships social public.